2014
DOI: 10.1016/j.pain.2013.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Pain-related musculoskeletal disorders, psychological comorbidity, and the relationship with physical and mental well-being in Gulf War veterans

Abstract: Occupational activities such as lifting loads, working in constrained spaces, and training increase the risk of pain-related musculoskeletal disorders (MSDs) in military veterans. Few studies have investigated MSD and psychological disorder in veterans, and previous studies had limitations. This cross-sectional study compared pain-related MSD and psychological comorbidity and well-being between 1381 male Australian 1990-1991 Gulf War veterans (veterans) and a military comparison group (n=1377, of whom 39.6% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Our cohort's mental health diagnoses were not as frequent as for subjects without arthritis, but this finding does not contradict previous findings that arthritis and PTSD and depression often co‐exist. Kelsall et al examined a cross‐sectional cohort of Gulf War (1990–1991) era veterans compared to military personnel who did not deploy in the Gulf War and determined that psychological conditions such as depression and PTSD were more common among the war veterans who had a musculoskeletal disorder as a comorbidity . Arthritis has been documented as associated with PTSD in several studies and with a number of sleep disorders …”
Section: Discussionmentioning
confidence: 99%
“…Our cohort's mental health diagnoses were not as frequent as for subjects without arthritis, but this finding does not contradict previous findings that arthritis and PTSD and depression often co‐exist. Kelsall et al examined a cross‐sectional cohort of Gulf War (1990–1991) era veterans compared to military personnel who did not deploy in the Gulf War and determined that psychological conditions such as depression and PTSD were more common among the war veterans who had a musculoskeletal disorder as a comorbidity . Arthritis has been documented as associated with PTSD in several studies and with a number of sleep disorders …”
Section: Discussionmentioning
confidence: 99%
“…Based on retrospective reporting, several studies have shown that military veterans with combat exposure and PTSD symptomatology may be more likely to have experienced previous childhood or adulthood traumas as well. 117;118 Thus, it is possible that the large association of adult-experienced trauma (e.g., combat exposure) with deleterious pain-related outcomes may reflect the cumulative effect of multiple historical traumas as well.…”
Section: Psychosocial Factors Influencing Pain-related Outcomesmentioning
confidence: 99%
“…Complicating pain in AD military personnel and veterans is the burden of other conditions such as sleep disturbances, fatigue, depression, anxiety, and posttraumatic stress disorder (PTSD) affecting physical and mental health (Higgins et al., ; McGeary, McGeary, Moreno, & Gatchel, ; Young‐McCaughan et al., ). Even evidence from Gulf War veterans affirms a significant relationship between pain‐related musculoskeletal disorders and reduced physical and mental well‐being (Kelsall et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…and mental health (Higgins et al, 2014;McGeary, McGeary, Moreno, & Gatchel, 2016;Young-McCaughan et al, 2017). Even evidence from Gulf War veterans affirms a significant relationship between pain-related musculoskeletal disorders and reduced physical and mental well-being (Kelsall et al, 2014).…”
mentioning
confidence: 99%